PROCESSING AND EXPORTING WOOD AND WOOD PRODUCTS IN VIETNAM - Thi Minh Ngoc, Vu; Quyen, Mai (Journal of Forestry Science and Technology, 2021)
In the past two decades, from 2000 to 2020, the export value of wood and wood products of Vietnam has increased from 219 million US dollars to 12.3 billion US dollars, which can be seen as a breakthrough development. However, not stopping there, the Vietnamese Government has assigned even higher targets for the wood industry in the coming years, which is 20 billion US dollars of export value in 2025. However, the wood and wood product processing and exporting of Vietnam still faces a number of shortcomings. By applying discriptive and comparative statistical methods, the article analyses the current situation of processing and exporting wood and wood products of Vietnam according to three stages: supply of raw materials, wood and wood product production, and wood and wood product export. Data mainly used in the article are extracted from officially domestic and international sources, such as data reported by the General Statistic Office, ITTO and FAO. Wood and wood products in this article includes roundwood, sawnwood, veneer, plywood (under HS44 group) and wooden furniture. At the same time, the achievements and challenges of the wood and wood product processing industry at each stage are also indicated. From there, some suggestions are made to help the wood and wood product industry in Vietnam overcome challenges and promote sustainable growth in the future.